Episode one: Tufts begins review of fossil fuel investment - Tufts Daily (Tufts Archival Research Center, 2021)
In this semester's first episode of The Rewind, host Leslie Gladstone interviews reporter Connor Dale and Tufts Climate Action representative Hanna Carr about the school's effort to review investments in its endowment.